1999
DOI: 10.1046/j.1365-2125.1999.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cholesterol reduction by simvastatin in diltiazem‐treated patients

Abstract: Patients who take both simvastatin and diltiazem may need lower doses of simvastatin to achieve the recommended reduction in cholesterol. The pharmacokinetic and pharmacodynamic aspects of this interaction need further study to confirm an enhanced effect on cholesterol reduction, and exclude an increased risk of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This may have important clinical implications for the cholesterol‐lowering response to simvastatin in individuals who are also taking verapamil or diltiazem. The results of a retrospective study reported previously by our group demonstrated that there was enhanced cholesterol reduction in patients who were taking simvastatin and diltiazem concurrently, and the interindividual variability in cholesterol‐lowering response to simvastatin was significantly lower for patients taking diltiazem than for patients not taking diltiazem [24]. To date, no studies have been reported regarding the effect of verapamil on the cholesterol‐lowering response to simvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…This may have important clinical implications for the cholesterol‐lowering response to simvastatin in individuals who are also taking verapamil or diltiazem. The results of a retrospective study reported previously by our group demonstrated that there was enhanced cholesterol reduction in patients who were taking simvastatin and diltiazem concurrently, and the interindividual variability in cholesterol‐lowering response to simvastatin was significantly lower for patients taking diltiazem than for patients not taking diltiazem [24]. To date, no studies have been reported regarding the effect of verapamil on the cholesterol‐lowering response to simvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…Coadministration of simvastatin with CYP3A inhibitors results in elevated plasma concentrations of the active simvastatin acid, which in turn is expected to elevate concentrations in tissues that correspond to sites of beneficial and unwanted effects. Rowland et al 47 demonstrated that the cholesterol‐lowering response to simvastatin was significantly greater (about 30%) in patients concomitantly receiving diltiazem. The incidence of simvastatin‐induced myopathy is low but may be significantly greater in patients treated with diltiazem.…”
Section: Discussionmentioning
confidence: 99%